Antioxidative, Antidiabetic, and Hypolipidemic Properties of Probiotic-Enriched Fermented Camel Milk Combined with Salvia officinalis Leaves Hydroalcoholic Extract in Streptozotocin-Induced Diabetes in Rats - Yousef M. Alharbi; Sally S. Sakr; Saleh M. Albarrak; Tariq I. Almundarij; Hassan Barakat; Mohamed F. Y. Hassan (MDPI AG, 2022)
Antioxidative, antidiabetic, and hypolipidemic properties of probiotic-enriched fermented camel milk (FCM) combined with Salvia officinalis L. leaves hydroalcoholic extract (SOHE) in streptozotocin-induced diabetes in rats were investigated. Phytochemicals analysis and antioxidant capacity indicated that S. officinalis contained high phenolics with super antioxidant activity. Subsequently, HPLC analysis demonstrated 13 phenolic acids and 14 flavonoids in considerable amounts with ferulic acid and resveratrol as predominant, respectively. The antidiabetic and hypolipidemic properties of FCM and SOHE were examined in a designed animal model consisting of seven treated groups for four weeks. There was a negative group (G1); the positive group (G2) received a single dose (50 mg kg−1) of streptozotocin (STZ) by intraperitoneal injection (i.p.); in G3, diabetic rats (DRs) orally received 5 mL FCM kg−1 daily; in G4, DRs orally received 50 mg GAE SOHE kg−1 daily; in G5, DRs orally received 5 mL FCM contains 25 mg GAE SOHE kg−1 daily; in G6, DRs orally received 5 mL FCM contains 50 mg GAE SOHE kg−1 daily; in G7, DRs orally received 50 mg metformin kg−1 daily. Combining FCM with SOHE at 25 or 50 mg kg−1 exhibited a synergistic effect in significantly lowering random blood glucose (RBG), fasting blood glucose (FBG), and improved weight gain recovery %. The hypolipidemic effect of FCM + 50 mg GAE SOHE kg−1 was significantly higher than using FCM or SOHE individually, and attenuation in triglycerides (TG), total cholesterol (CHO), and high- and low-density lipoproteins (HDL and LDL), and very-low-density lipoproteins (VLDL) was remarked. Combining FCM with SOHE at 25 or 50 mg kg−1 ameliorated liver and kidney functions better than individual uses of FCM, SOHE, or metformin. Interestingly, FCM with 50 mg SOHE kg−1 presented significant improvement in the activity of antioxidant enzymes, reduced glutathione (GSH), catalase (CAT), superoxide dismutase (SOD), and a substantial reduction in malonaldehyde (MDA) levels with 53.75%, 89.93%, 63.06%, and 58.69% when compared to the STZ group (G2), respectively. Histopathologically, administrating FCM + 25, 50 mg SOHE kg−1 or 50 mg kg−1 metformin showed a normal histological structure of both islets of Langerhans cells and acini. In conclusion, combining FCM with SOHE presented synergistic and therapeutical efficacy. It could be beneficial and profitable for controlling diabetes mellitus complications and protecting against oxidative stress.